(untitled) - Režný, Pavel (Aura musica, 2021)
The article is focused on selected moments from the twenty-year history of the Ateneo Mixed Chamber Choir of Palacký University in Olomouc. It deals with important events and concerts in the life of the choir. It also brings a selection of the most important foreign performances of the choir and a selection of CDs on which SKS Ateneo UP Olomouc sings.
Keywords: Mixed choir; Ateneo; Palacký University; Olomouc; choral festival; CD; concert; workshop; choirmaster; Festa Academica; Department of Music; Corpus Christi Chapel; Be2gether; International Visegrad Fund; Pavel Rezny; Arts Centre UP